Sedimentologic to metamorphic processes recorded in the high-pressure/low-temperature Mesozoic Rosetta Marble of Anatolia - Scheffler, F.; Oberhänsli, R.; Pourteau, Amaury; Immenhauser, A.; Candan, O. (2016)
© 2015, Springer-Verlag Berlin Heidelberg. Anatolia’s high-pressure metamorphic belts are characterized in part by a Neotethyan stratigraphic succession that includes a mid-Cretaceous hemi-pelagic marble sequence. This unit contains, towards its stratigraphic top, dm-to-m-long radiating calcitic rods forming rosette-like textures. Here, we refer to these features as “Rosetta Marble”. The remarkable textural similarity of non-metamorphic selenite crystals and radiating calcite rods in the Rosetta Marble strongly suggests that these textures represent pseudomorphs after selenites. Metamorphosed hemi-pelagic limestones, dominated by Rosetta selenite pseudomorphs, are alternating with siliceous meta-sediments containing relictic radiolaria tests. This stratigraphic pattern is indicative of transient phases characterized by evaporites precipitated from basinal brines alternating with non-evaporative hemi-pelagic deposition from normal-marine seawater. The regional distribution of Rosetta Marble exposures over 600 km is indicative of basin-scale evaporitic intervals. High-pressure, low-temperature metamorphism of these rocks is witnessed by Sr-rich (up to 3500 ppm), fibrous calcite pseudomorphs after aragonite and isolated aragonite inclusions in quartz. Peak metamorphic conditions of 1.2 GPa and 300–350 °C are attested by high-Si white mica thermobarometry. The Rosetta Marble case example examines the potential to unravel the complete history from deposition to diagenesis and metamorphism of meta-sedimentary rocks.